2004
DOI: 10.1590/s0074-02762004000100010
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of Venezuelan patients with severe mucocutaneous or early lesions of diffuse cutaneous leishmaniasis with a vaccine containing pasteurized Leishmania promastigotes and bacillus Calmette-Guerin: preliminary report

Abstract: Severe mucocutaneous (MCL) and diffuse (DCL) forms of American cutaneous leishmaniasis (ACL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 23 publications
2
45
0
2
Order By: Relevance
“…Immunotherapeutic approaches may be more effective as they require shorter treatment periods, and the induction of multiple effector mechanisms against the parasite may lower the possibilities of resistance. Therapeutic vaccines have indeed shown promise for the control of several infectious diseases [8][9][10][11][12][13][14][15]. In the case of T. cruzi, we showed that a therapeutic DNA vaccine encoding parasite antigens can lead to a reduction in parasitemia and disease severity in BALB/c and ICR mice infected with an otherwise lethal dose of parasites [16].…”
Section: Introductionmentioning
confidence: 82%
“…Immunotherapeutic approaches may be more effective as they require shorter treatment periods, and the induction of multiple effector mechanisms against the parasite may lower the possibilities of resistance. Therapeutic vaccines have indeed shown promise for the control of several infectious diseases [8][9][10][11][12][13][14][15]. In the case of T. cruzi, we showed that a therapeutic DNA vaccine encoding parasite antigens can lead to a reduction in parasitemia and disease severity in BALB/c and ICR mice infected with an otherwise lethal dose of parasites [16].…”
Section: Introductionmentioning
confidence: 82%
“…There is general agreement, however, that there is a high predominance of CD4+ Th2 immune response in these patients, which has resulted in ADCL being regarded as a polar form of ACL. The view that has been expressed in most situations is that MCL is an intermediate form between LCL and ADCL and, consequently, the disease has been linked to a mixture of Th1 and Th2 immune responses (Convit et al 2004). We feel it more correct, however, to regard MCL and ADCL as polar forms of ACL, in the hypersensitivity pole (high Th1 immune activation) and the hyposensitivity pole (high Th2 immune activation), respectively, with LCL (moderate Th1 immune activation) occupying the middle of this spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Embora haja muitos grupos trabalhando na tentativa de desenvolvê-la (Convit et al, 2004;Tewary et al, 2004) ainda há vários fatores que difi cultam, tais como os mecanismos efetores da resposta imune no homem, além de obstáculos de ordem política e econômica (Handman, 1997). Devido a essas difi culdades, torna-se importante a busca por novos agentes quimioterápicos.…”
Section: Introductionunclassified